Situation Report: Romania, 12 December 1975 - Radio Free Europe/Radio Liberty Research Institute (RFE/RL Research Institute)
An information bulletin produced by Radio Free Europe based on extensive monitoring of communist bloc news outlets and primarily intended for internal circulation. Pieces were generally contributed by the staff of the research and analysis departments and treated current affairs in the region. Cultural Information Policy Becoming Increasingly Restrictive? Historical Film Pursues Propaganda Goals Romania and the MBFR Talks in Vienna West German Foreign Minister Genscher Visits Bucharest 1976 Trade and Payments Agreement with Hungary Signed Romanian Airlines Inaugurate Flights to Peking [Beijing] and Amman